Cr(OH)(3)(s) Oxidation Induced by Surface Catalyzed Mn(II) Oxidation - Namgung, Seonyi; Kwon, Man Jae; Qafoku, Nikolla P.; Lee, Giehyeon (American Chemical Society, 2014)
We examined the feasibility of Cr(OH)(3)(s) oxidation mediated by surface catalyzed Mn(II) oxidation under common groundwater pH conditions as a potential pathway of natural Cr(VI) contaminations. Dissolved Mn(II) (50 ?M) was reacted with or without synthesized Cr(OH)(3)(s) (1.0 g/L) at pH 7.0-9.0 under oxic or anoxic conditions. Homogeneous Mn(II) oxidation by dissolved O2 was not observed at pH ? 8.0 for 50 days. At pH 9.0, by contrast, dissolved Mn(II) was completely removed within 8 days and precipitated as hausmannite. When Cr(OH)(3)(s) was present, this solid was oxidized and released substantial amounts of Cr(VI) as dissolved Mn(II) was added into the suspension at pH ? 8.0 under oxic conditions. Production of Cr(VI) was attributed to Cr(OH)(3)(s) oxidation by a newly formed Mn oxide via Mn(II) oxidation catalyzed on Cr(OH)(3)(s) surface. XANES results indicated that this surface-catalyzed Mn(II) oxidation produced a mixed valence Mn(III/IV) solid phase. Our results suggest that toxic Cr(VI) can be naturally produced via Cr(OH)(3)(s) oxidation coupled with the oxidation of dissolved Mn(II). In addition, this study evokes the potential environmental hazard of sparingly soluble Cr(OH)(3)(s), which has been considered the most common and a stable remediation product of Cr(VI) contamination.
Keywords: BIOGENIC MN-OXIDES; SP STRAIN SG-1; MANGANESE(II) OXIDATION; MARINE BACILLUS; CHROMIUM(III) OXIDATION; HEXAVALENT CHROMIUM; REDUCTIVE TRANSFORMATION; AQUEOUS MN(II); NATURAL-WATERS; KINETICS